Quantification of Thyroid Viscosity in Healthy Subjects Using Ultrasound Shear Wave Dispersion (Viscosity PLUS) - Dana Stoian; Luciana Moisa; Laura Taban; Ioan Sporea; Alexandru Popa; Felix Bende; Alina Popescu; Andreea Borlea (Diagnostics, 2022)
Shear-wave elastography (SWE) is widely used in thyroid evaluation, but multiple factors influence thyroid stiffness. Estimating tissue viscosity may enhance the ultrasound diagnosis of thyroid diseases, along with the ultrasound (US) and the SWE assessment. In order to be able to detect diffuse thyroid disease by viscosity measurements, it is essential to firstly define the normal values of thyroid viscosity in healthy subjects. Currently there are no published data on thyroid viscosity measurements. This first prospective study aimed to determine the normal range of thyroid viscosity values in a cohort of healthy thyroids, as well as to determine the factors that may influence them. One hundred and twenty-one consecutive subjects without thyroid pathology were evaluated in the study by means of conventional ultrasound, two-dimensional SWE (2D SWE PLUS) and viscosity plane-wave ultrasound (ViPLUS) embedded in the Supersonic MACH® 30 ultrasound system. Five valid tissue viscosity measurements were obtained for each thyroid lobe in every patient and the median values were analyzed and correlated with the biological and demographic parameters of each patient. Our results reveal that ViPLUS is a highly feasible and reproducible technique for thyroid evaluation. Thyroid stiffness, age, gender, BMI and depth of measurements did not influence the thyroid viscosity values. The mean thyroid viscosity by ViPLUS for normal thyroid tissue was of 2.42 ± 0.41 Pa·s. Viscosity assessment by Supersonic ViPLUS is an innovative, non-invasive technique that has proven to be useful for thyroid US evaluation and remains to demonstrate its effectiveness in identifying patients with thyroid disease.